2016
DOI: 10.7899/jce-15-25
|View full text |Cite
|
Sign up to set email alerts
|

A focus group study of chiropractic students following international service learning experiences

Abstract: Objective: One objective of chiropractic education is to cultivate clinical confidence in novice practitioners. The purpose of this qualitative study was to describe how participation in a short-term international service learning experience changed perceptions of clinical confidence in senior chiropractic students. Methods: Seventeen senior chiropractic students participated in 4 moderated focus group sessions within 4 months after a clinical educational opportunity held in international settings. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Community organizations that offer service learning opportunities may want to add information to their trainings about how events, such as natural disasters, can impact a student’s experience. While service learning in itself can serve as a form of training for health professional students by giving them hands-on opportunities to work with individuals in need (Boysen, Salsbury, Derby, & Lawrence, 2016), there is also a need for adequate training upfront that provides students with information on a variety of events that could happen. Prior research has demonstrated that providing intensive training that addresses student concerns around what to expect before service learning assignments occur could decrease student apprehension related to completing service learning requirements (Chuang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Community organizations that offer service learning opportunities may want to add information to their trainings about how events, such as natural disasters, can impact a student’s experience. While service learning in itself can serve as a form of training for health professional students by giving them hands-on opportunities to work with individuals in need (Boysen, Salsbury, Derby, & Lawrence, 2016), there is also a need for adequate training upfront that provides students with information on a variety of events that could happen. Prior research has demonstrated that providing intensive training that addresses student concerns around what to expect before service learning assignments occur could decrease student apprehension related to completing service learning requirements (Chuang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated that providing intensive training that addresses student concerns around what to expect before service learning assignments occur could decrease student apprehension related to completing service learning requirements (Chuang et al, 2015). Students may also benefit from a debriefing session after the volunteer assignment to talk about their experiences (Boysen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…CSL provides for fostering of civic engagement, fostering of caring, introduction to diversity issues, transformative learning, and awareness of role (Bowen, 2014; Boysen et al, 2016; Fullerton et al, 2015; Greenwood, 2015). Higgins (2009) suggests that CSL instills a sense of civic responsibility in students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These concrete experiences followed by focused reflection allow for enhanced understanding and knowledge development. This approach has been used widely throughout higher education because of its varied benefits, including fostering civic engagement, fostering caring, introducing issues of diversity, fostering awareness of role, and strengthening communication and collaboration within the community (Bowen, 2014; Boysen et al, 2016; Fullerton et al, 2015; Greenwood, 2015; Ponder et al, 2011). CSL experiences are commonly utilized as required coursework in both traditional undergraduate and honors undergraduate curricula to enhance student awareness, civic engagement, and understanding of social justice issues (Klos et al, 2015).…”
mentioning
confidence: 99%
“…Little has been published, however, about service learning in doctor of chiropractic programs (DCPs), with the exception of a small study on student outcomes after international mission trips. 7 Since spring 2017, the introductory public health course at our institution has included a service-learning assignment in which students are given a choice to volunteer for a nonprofit, attend a political event, or work on a project related to health in their community (Appendix A is available online accompanying this paper at www. journalchiroed.com).…”
Section: Introductionmentioning
confidence: 99%